RESULTADOS OBTIDOS NA PESQUISA EM MECANIZAÇÃO DA AGRICULTURA FAMILIAR NO PERÍODO 2011 - Locatelli, Giovani; Valdiero, Antonio C.; Cabral, Paulo E. d. O.; Stoffel, Pablo B. (Salão do Conhecimento, 2013)
Resumo